جوانب الرحمة في حقوق غير المسلمين في المجتمع الإسلامي: الدستور الأول للإسلام نموذجًا = Aspek Kasih Sayang Dalam Hak Orang Bukan Islam dalam Masyarakat Islam : Perlembangaan Pertama Model Islam (Kajian, Deskriptif, Analisis) - Khan, Musaddiq Majid (Jil Sceientific Research Centr, 2016)
Since the creation of the universe and its inhabitants, Allah the almighty has not left them clueless in their affairs, rather He has sent his messengers to guide them and to remind them about the purpose of their creation. Of all the messengers Allah the almighty sent, Prophet Muhammad (May the peace and blessings be upon Him) was the last one. The message brought by Him (PBUH) was not something new to what had been revealed before instead it was reformation of misconstruction and alteration created by the followers of the previous messengers. The state of that message was called al-IslÉm (Total Submission). And Allah the almighty made al-Islam a complete and comprehensive way of life for the guidance of all mankind, not a single aspect of life has been left without providing the vibrant directions. This is the fact which makes Islam bondsman for the all necessities of mankind; worldly, hereafter, material and spiritual. In this regard Islam does not make any distinction between the religion and world, form and soul. In fact living life according to the Shariah is Islam. This concept highlights the characteristics of compassion and mercy for all the humanity. This paper will deliberate on one class of the human society, those who prefer to live under the IslÉmic Shariah. This study willl discuss the rights that Islam has bestowed them with and the application of these rights.